MENGKOMUNIKASIKAN PERSPEKTIF PEREMPUAN DALAM AL-QUR`AN - Takbir Takbir (Jurnal Dakwah Tabligh, 2015)
God created women and men to complement each other in this kehidpuan wading. When discuss women in the Islamic tradition, namely the restriction of the discussion on the vision of al-Qur`an about women. This is due to several reasons. First, in contrast to the hadith, al-Qur`an is the source of Islamic values that authenticity was never debated. Women are natural reality. How to treat women against him, it's named, or produce social reality. If a husband making out with his wife (woman) does not occur any pornographic event. The new pornography occurs when someone peeping incident, because "the Shari'a peek" breaking "nature of the nudity of love". Pornography also occurs when women indulgence in private parts to the man who was not her husband. Al-Qur`an does not treat women as discriminatory. Gender does not distinguish degrees, nor any law applies equally to men and women. There are no differences in the characteristics between women and men. The size value is the same for men and women. Al-Qur`an not describe the physical beauty as an ideal value for women. Al-Qur`an teaches women to cover even their physical beauty (to close the genitals). As the ideal value lies in piety, purity, and stubbornness in maintaining confidence